2016
DOI: 10.1111/jeu.12356
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by Time During an Arctic Phytoplankton Spring Bloom

Abstract: The arctic phytoplankton spring bloom, which is often diatom-dominated, is a key event that provides the high latitude communities with a fundamental flux of organic carbon. During a bloom, phytoplankton may increase its biomass by orders of magnitude within days. Yet, very little is known about phytoplankton bloom dynamics, including for example how blooming affects genetic composition and diversity of a population. Here, we quantified the genetic composition and temporal changes of the diatom Fragilariopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 101 publications
(96 reference statements)
2
11
0
Order By: Relevance
“…2A), with diatoms dominating in spring and dinoflagellates afterwards. This supports previous observations of diatoms dominating the spring bloom biomass, which then quickly consume the nutrients in the mixed layer (Tammilehto et al, 2017), giving way to mixotrophic organisms such as dinoflagellates in the summer period (Raymont, 1980;Smayda and Trainer, 2010;Flynn et al, 2019). This is in accordance with our data, where the nutrients in the spring season were quickly depleted in correlation with high diatom abundance in the microplankton size fraction (Figs.…”
Section: Seasonality In Context Of Nutrient Availabilitysupporting
confidence: 93%
“…2A), with diatoms dominating in spring and dinoflagellates afterwards. This supports previous observations of diatoms dominating the spring bloom biomass, which then quickly consume the nutrients in the mixed layer (Tammilehto et al, 2017), giving way to mixotrophic organisms such as dinoflagellates in the summer period (Raymont, 1980;Smayda and Trainer, 2010;Flynn et al, 2019). This is in accordance with our data, where the nutrients in the spring season were quickly depleted in correlation with high diatom abundance in the microplankton size fraction (Figs.…”
Section: Seasonality In Context Of Nutrient Availabilitysupporting
confidence: 93%
“…Similar patterns of genetic differentiation between years were observed in marine dinoflagellates (Dia et al, 2014) and freshwater raphidophytes (Lebret et al, 2012). Other studies showed that genetic diversity can rapidly change over the course of microalgal blooms, causing significant intra-annual genetic differentiation (Rynearson et al, 2006;Erdner et al, 2011;Richlen et al, 2012;Tammilehto et al, 2016;Ruggiero et al, 2017). Such changes in population structure can occur on temporal scales from a few days to a few months.…”
Section: Introductionsupporting
confidence: 61%
“…Whether the three P. galaxiae populations are separate species needs further investigation, but the coherent pattern observed in size ranges, genetics and timing of the blooms provides a further possible case of isolation by time and allochronic speciation processes. Genetic divergence among populations occurring at different times has been observed in various phytoplankton groups 11,[58][59][60][61] , suggesting that temporal segregation could be a general mechanism for speciation in marine protists. Yet phenology has rarely been considered a stable, endogenous character in phytoplankton, whereby the alternation of different species over the seasons is postulated to be strictly driven by changes in environmental conditions.…”
Section: Discussionmentioning
confidence: 99%